Community Perception of Non-Beneficiaries on the Department of Social Welfare and Development (DSWD) Sustainable Livelihood Program in the Municipality of Bansalan, Davao Del Sur - Supat, Crystal Khayette; Apas, Roel (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to evaluate community perceptions of non-beneficiaries regarding the effectiveness of the Department of Social Welfare and Development (DSWD) Sustainable Livelihood Program (SLP) in the Municipality of Bansalan, Davao del Sur. Despite numerous evaluations of SLP beneficiaries, limited research exists on how non-beneficiaries perceive its effectiveness, which this study sought to address. Specifically, the research examined the socio-economic profiles of respondents and their perceptions of the program’s impact. Utilizing a quantitative descriptive-comparative survey design, the study employed simple random sampling to ensure fair representation and gathered data from 99 respondents. Statistical tools, including frequency, relative frequency distribution, mean, and ANOVA, were applied for data analysis. The results indicated that the community perceives the DSWD-SLP as significantly beneficial, with an overall mean effectiveness score of 4.22, interpreted as “very high”. This suggests that even non-beneficiaries recognize the positive contributions of the program toward sustaining livelihoods in the local community. Furthermore, socio-economic profile factors, including age, gender identity, civil status, educational attainment, and monthly income, were found to have no significant influence on community perceptions of the program’s effectiveness. The major conclusion is that the DSWD-SLP has garnered broad community support and visibility, extending beyond its direct beneficiaries. Practically, this implies a positive public perception that may support the program’s expansion and improved targeting. Socially, it highlights the importance of inclusive program awareness and transparency, which can enhance community trust and cooperation in future livelihood.